Short-sweep capillary electrophoresis with a selective zinc fluorescence imaging reagent FluoZin-3 for determination of free and metalothionein-2a-bound Zn2+ ions - Nejdl, Lukas; Moravanska, Andrea; Smerkova, Kristyna; Mravec, Filip; Krizkova, Sona; Pomorski, Adam; Krężel, Artur; Macka, Mirek; Adam, Vojtech; Vaculovicova, Marketa (Analytica chimica acta, 2018)
A capillary electrophoretic (CE) method using a short-sweep approach and laser-induced fluorescence (LIF) detection (ShortSweepCE-LIF) was developed for determination of Zn2+ and Cd2+ as complexes with highly selective and sensitive fluorescent probe FluoZin-3. The ShortSweepCE-LIF method, established in this work, can be used for examining competitive Zn2+ and Cd2+ binding properties of metalloproteins or peptides. The parameters including background electrolyte composition, injection pressure and time as well as separation voltage were investigated. Under the optimized conditions, 80 mM HEPES, pH 7.4, with 1.5 μM FluoZin-3 was used as an electrolyte, hydrodynamic injection was performed at 50 mbar for 5 s, and separation voltage of 25 kV. Limits of detection for Zn2+ and Cd2+ were 4 and 125 nM, respectively. The developed method was demonstrated in a study of interactions between metalothionein-2a isoform and metal ions Zn2+, Co2+ and Cd2+. It was found that FluoZin-3 was able to extract a single Zn2+ ion, while added Co2+ (in surplus) extracted only 2.4 Zn2+ ions, and Cd2+ extracted all 7 Zn2+ ions present in the metalothionein molecule.
Keywords: kadmium; zinek; Optical Imaging; metalothionein; Metal ions; Fluorescent Dyes; Metallothionein; fluorescenční barviva; ionty; Metalothionein; Capillary electrophoresis; polycyklické sloučeniny; Electrophoresis, Capillary; Zinc; Polycyclic Compounds; optické zobrazování; Ions; Cadmium; FluoZin-3; elektroforéza kapilární